Effects of gluteal kinesio-taping on performance with respect to fatigue in rugby players. Issue 2 (17th February 2016) - Strutzenberger, Gerda; Moore, Joseph; Griffiths, Hywel; Schwameder, Hermann; Irwin, Gareth
Abstract: Kinesio-tape ® has been suggested to increase blood circulation and lymph flow and might influence the muscle's ability to maintain strength during fatigue. Therefore, the aim of this study was to investigate the influence of gluteal Kinesio-tape ® on lower limb muscle strength in non-fatigued and fatigued conditions. A total of 10 male rugby union players performed 20-m sprint and vertical jump tests before and after a rugby-specific fatigue protocol. The 20-m sprint time was collected using light gates (SMARTSPEED). A 9-camera motion analysis system (VICON, 100 Hz) and a force plate (Kistler, 1000 Hz) measured the kinematics and kinetics during a counter movement jump and drop-jump. The effect of tape and fatigue on jump height, maximal vertical ground reaction force, reactivity strength index as well as lower limb joint work were analysed via a two-way analysis of variance. The fatigue protocol resulted in significantly decreased performance of sprint time, jump heights and alterations in joint work. No statistical differences were found between the taped and un-taped conditions in non-fatigued and fatigued situation as well as in the interaction with fatigue. Therefore, taping the gluteal muscle does not influence the leg explosive strength after fatiguing in healthy rugby players.